Successful cognitive aging definitions and associated demographic, biomarker profiles and lifestyles in the 80+ MCSA population. (31st December 2021) - Arenaza‐Urquijo, Eider M; Castillo, Anna; Przybelski, Scott A.; Lesnick, Timothy G.; Pillai, Sheela Kumari Raghavan; Mielke, Michelle M.; Machulda, Mary M.; Knopman, David S.; Radford, Jonathan Graff; Jack, Clifford R.; Petersen, Ronald C.; Vemuri, Prashanthi
Abstract: Background: There have been no standard definitions of successful cognitive aging (SA). Our goal was to apply different SA definitions to the 80+ population in the Mayo Clinic Study of Aging (MCSA) on the basis of (i) cross‐sectional vs longitudinal cognition ("Exceptionality" vs "Maintenance") and (ii) memory vs global cognitive scores and explore the participant characteristics for each SA definition on the basis of baseline imaging markers and mid/late‐life health. Method: We included 2157 participants from the MCSA, all ≥80 years at baseline and classified them into two SA definitions using memory z‐scores or global z‐scores: "Exceptionality" when high cognitive performance was observed (z‐scores ≥ 1 SD), "Maintenance" when cognitive function was preserved over time (Slope ≥ ‐0.1/year using mixed‐effect models). Our imaging markers were: PET‐based amyloid positivity (A+), MRI‐based neurodegeneration positivity (N+), WMH, FDG‐PET SUVR markers of resilience (anterior cingulate, ACC) and AD‐related areas (posterior cingulate). We also examined APOE4 status and other health characteristics. Group comparison was performed within each definition (e.g. exceptional vs non‐exceptional memory) using ANCOVA and binary logistic regressions with adjustments for age, sex, and education. Result: A lower number of participants met the "Exceptionality" criteria (10%: memory and 4%: global). A greater number met the "Maintenance" criteria (53%: memory and 32%: global). Less than 7% showed both "Exceptional" cognition and "Maintenance" over time. Participants across SA definitions were in general younger, more often women, with a higher education/occupation and less often APOE4 carriers. All SA groups showed higher ACC metabolism and lower N+ compared to the corresponding non‐SA group. More than 50% of the participants in the "Exceptional" groups were A+ (57%: memory, 50%: global). A+ frequency was significantly lower in the "Maintainers" (<42%). Better mid/late‐life health indicators were observed in the SA groups, including lower cardio‐metabolic conditions, higher mid‐life cognitive activities, lower depressive symptomatology, lower hypersomnolence and better self‐perception of health. Conclusion: Different SA definitions identified mainly non‐overlapping 80+ groups that showed several common features including higher education/occupation, percent of women, better lifestyles, lower N+ frequency, and higher ACC metabolism. Lower A+ frequency was a key distinct feature of "Maintenance".